A Review on Electrode Materials of Fast‐Charging Lithium‐Ion Batteries. Issue 10 (25th July 2022) - Zhang, Zhen; Zhao, Decheng; Xu, Yuanyuan; Liu, Shupei; Xu, Xiangyu; Zhou, Jian; Gao, Fei; Tang, Hao; Wang, Zhoulu; Wu, Yutong; Liu, Xiang; Zhang, Yi
Abstract: In recent years, the driving range of electric vehicles (EVs) has been dramatically improved. But the large‐scale adoption of EVs still is hindered by long charging time. The high‐energy LIBs are unable to be safely fast‐charged due to their electrode materials with unsatisfactory rate performance. Thus it is necessary to summarize the properties of cathode and anode materials of fast‐charging LIBs. In this review, we summarize the background, the fundamentals, electrode materials and future development of fast‐charging LIBs. First, we introduce the research background and the physicochemical basics for fast‐charging LIBs. Second, typical cathode materials of LIBs and the method to enhancing their fast‐charging properties are discussed. Third, the anode materials of LIBs and the strategies for improving their fast‐charging performance are analyzed. Finally, the future development of the cathode materials in fast‐charging LIBs is prospected. Abstract : The typical cathode materials and anode materials of LIBs and the strategies for improving their fast‐charging performance.